Exploración del potencial catalítico de Metal-Organic Frameworks con sitios de coordinación insaturados en síntesis orgánica - Báez Gómez, Reynier (2024)
In recent years, Metal-Organic Frameworks (MOFs) have gained relevance in various applications, they stand out in heterogeneous catalysis due to their unique properties, such as high porosity and specific surface area, thermal stability, and the ability to incorporate catalytically active centers. In this work, the synthesis, characterization, and catalytic evaluation of four MOFs were carried out: HKUST-1, MIL-101(Cr), UiO-66-NH2, and MIL-53(Al). The synthesis of MIL-53(Al) through up-cycling from aluminum cans and PET bottles is particularly notable, promoting the circular economy by demonstrating the feasibility of producing MOFs from waste materials. MOFs were evaluated as heterogeneous catalysts in two C-N bond-forming reactions. For the first time, MOFs were reported as catalysts in the synthesis of acylhydrazides from aldehydes and azocompounds. The reaction was carried out at 60 °C for 48 hours in ethyl acetate, obtaining 16 compounds with yields ranging from 54 % to 97 %. The synthesis of pyrroles via the Paal-Knorr reaction from anilines and acetylacetone was also studied. The reaction was conducted under solvent-free conditions using microwave irradiation for 5 minutes, producing 7 pyrroles with yields between 50 % and 96 %. In both reactions, MIL-53(Al) proved to be the most efficient catalyst, with catalyst loads of 10 mol % and 5 mol %, respectively. Additionally, the stability and reusability of MIL-53(Al) were evaluated over four consecutive catalytic cycles, maintaining its performance with minimal decline. The combination of high catalytic activity, stability, and sustainable origin of MIL- 53(Al) represents a significant advancement in heterogeneous catalysis and green chemistry. The pioneering application of MOFs in the synthesis of hydrazides expands the frontiers of catalysis with these materials, providing a clear example of how the principles of the circular economy and catalysis innovation can be applied in the synthesis of advanced materials and the development of more efficient and environmentally friendly chemical processes.